The unicorn quest - Benko, Kamilla (Benko, Kamilla. Unicorn quest., 2018)
In an antique-filled mansion, sisters Claire and Sophie find a ladder to the magical land of Arden, where wraiths roam freely, unicorns have disappeared, and the guilds of magic no longer trust each other.